Al-Simā ‘Inda Sībawaih fī Ushul An-Nahwi - Ika Mahmudah Fauziah; Maman Abdurrahman; Asep Sopian (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2021)
Al-simāʿ (linguistic attestation) constitutes one of the fundamental principles in the development of Arabic grammatical theory and serves as the primary basis for establishing its rules and methodological framework. Rather than being a simple process of listening, al-simāʿ involves a systematic and rigorous linguistic procedure that begins with the collection of authentic language data and proceeds through classification, categorization, comparison, and inductive analysis before arriving at grammatical principles. Consequently, al-simāʿ represents the essential empirical foundation upon which Arabic grammar is constructed. This study examines the role of al-simāʿ in the formulation of Arabic grammatical theory and its relationship with other methods of grammatical reasoning. Using a qualitative library research approach, the study analyzes classical Arabic grammatical literature to explore how authentic linguistic evidence is employed in establishing grammatical rules. The findings indicate that al-simāʿ extends beyond the mere collection of linguistic evidence. It functions as the basis for subsequent analytical methods, including qiyās (analogy), taʿlīl (causal explanation), taqsīm (classification), istikrāʾ (induction), and other forms of grammatical inference. These methods are utilized either to validate grammatical rules or to explain and evaluate linguistic phenomena. The study also highlights the significant contribution of Sibawayh, whose pioneering work laid the foundation of Arabic grammar through the systematic application of al-simāʿ and rational analysis. His masterpiece, Al-Kitāb, became a landmark in the history of Arabic linguistics and established methodological standards that profoundly influenced the Basran school of grammar and subsequent generations of Arab grammarians.